Pyrrolizidine alkaloid profiling of four Boraginaceae species from Northern Germany and implications for the analytical scope proposed for monitoring of maximum levels. Issue 8 (2nd August 2020) - Mädge, Inga; Gehling, Matthias; Schöne, Cindy; Winterhalter, Peter; These, Anja
ABSTRACT: Pyrrolizidine alkaloids (PAs) and their corresponding N -oxides (PANOs) have been determined in food and feed at levels relevant for consumer health. More than 660 different PAs have been detected, but few are available as reference substances for analytical demands. In the context of the European legislation on maximum levels of PAs in food products, a defined analytical scope of 21 PAs for determination has been suggested. An expansion of the scope from 21 to 35 PAs, including 14 structural isomers, is currently under discussion. In the present study, a target screening method was established for a comprehensive characterisation of PA profiles of the species Echium vulgare, Heliotropium europaeum, Cynoglossum officinale and Symphytum spp. to assess whether an expansion of the analytical scope is required to quantitatively cover the total PA contents of Boraginaceae species. The scope of the method comprised known and unknown PAs previously screened and confirmed in the respective plant extracts. A total of 176 PAs and PANOs were detected. The toxic 1, 2-unsaturated PAs represent the predominant PA type with about 98% of the mean total content. This PA profiling demonstrates that an expansion of the scope from 21 to 35 PAs is required to adequately cover the mean total PA contents of Cynoglossum officinale and H. europaeum, whereas in the case of Symphytum spp. and Echium vulgare an expansion would not be necessary. Abbreviations: Pyrrolizidine alkaloid: PA, Pyrrolizidine alkaloid N -oxide: PANO, European Food Safety Authority: EFSA, German Federal Institute for Risk Assessment: BfR, ultra-high performance liquid chromatography: UHPLC, high-resolution: HR, tandem mass spectrometer: MS/MS, multiple reaction monitoring: MRM, data-independent MS2: ddms2, electrospray ionisation: ESI, limit of detection: LOD, limit of quantification: LOQ, gas chromatography coupled with mass spectrometry: GC-MS, fragmentation (data): MS2 (data), full scan: MS1, variable data-independent acquisition: vDIA, monoester esterified with a necic acid at position C9 of the necine base: O 9 -monoester, relative proportion: rel. prop., intraperitoneal: i.p., intravenous: i.v., higher-energy C-trap dissociation: HCD, all-ion fragmentation: AIF, parallel reaction monitoring: PRM